Community-based entrepreneurship: Evidences from a retail case study - Sazzad Parwez (Journal of Innovation and Entrepreneurship, 2017)
Community-based entrepreneurship is considered to be an important instrument for the realization of potential among marginal and deprived communities isolated from the mainstream economy and is important in bringing social upliftment. Cultural values, shared resources, linkages, and mutual trust work for the community, nurtured through close personal relations for the functioning of economic activities. Entrepreneurial activities creating local public goods for a community have a comparative advantage over the absolute market-oriented activities. This paper tries to follow a case study method to analyze the community-based entrepreneurship in a marginal community (Muslim). Many self-employed Muslim workers and small businesses in urban centers in a non-Islamic society indicate that they bound to have a great propensity for entrepreneurship compared to the indigenous population. The government needs to introduce a policy with implicative measures for financial and technical support to these entrepreneurial activities.
Keywords: 650; Community; Entrepreneurship; Friendly Mart; Muslim; Retail